Restore water resources, diversify vegetation or control invasive species? How to effectively manage wetland based on carbon trading - Tan, Bo; Bai, Yuntao (Frontiers in Ecology and Evolution, 2025)
Wetland ecosystems have suffered serious damage. To increase the incentive to protect wetlands, the government can allocate certain carbon emission allowances to environmental organizations that protect wetlands. Common wetland governance modes include restoring water quantity, diversifying vegetation and controlling invasive species. In order to derive the applicable range of various wetland governance modes, this article constructs three differential game models and compares and analyzes the equilibrium results obtained by the models. Finally, the research shows that if the additional reputation gained by restoring water quantity per unit is small, the government can achieve the maximum benefit by choosing the restoring water quantity mode. If the additional reputation gained by restoring water quantity per unit is large, the government can achieve the maximum benefit by choosing the diversifying vegetation mode. Due to the existence of carbon trading, environmental organizations will take wetland ecosystem protection measures. If the additional reputation gained by restoring water quantity per unit is small and the revenue gained by governing wetlands per unit is large, the environmental organizations can achieve the maximum benefit by choosing the controlling invasive species mode. Otherwise, the environmental organizations can achieve the maximum benefit by choosing the diversifying vegetation mode.